Exocrine Pancreatic Function Tests: A Review - Yuyuan Li; Stephen G. Chiverton; Richard H. Hunt (Canadian Journal of Gastroenterology)
Exocrine pancreatic function tests (PFTs) remain of value in the diagnosis and assessment of chronic pancreatic disease. Direct intubation PFTs, using secretin/cholecystokinin or secretin/caerulein as the stimulants, continue to the the 'gold standard', although they are invasive, expensive and time consuming. Tubeless indirect tests, ie, the N-benzoyl-L-tyrosyl-para-aminobe-zoic acid and pancreolauryl tests, have gained increasing acceptance particularly as screening tests. The fecal measurement of chymotrypsin remains a useful screening test for pancreatic insufficiency and fecal fat testing standard for steatorrhea. Radioisotope tests are now outdated. Estimation of pancreatic markers in serum, urine and body fluids are useful when abnormal hut miss mild disease. Combining PFTs with imaging techniques provides a rational approach to early diagnosis and gives a better assessment of the patient with chronic pancreatic disease.